PEMIKIRAN TENTANG PENERJEMAHAN KOLABORATIF - Aveling, Harry (Kementerian Sekretariat Negara Republik Indonesia, 2014)
This article deals with the potentials and problems of co-translation, the production of a target text by two people: one who knows the source language and another who does not. It argues that the processes of translation and co-translation are identical once a preliminary initial target text translation (a